Information behavior of cum laude graduates at Universitas Riau in 2020 - Wati, Mega; Safii, Moh.; Martutik, Martutik (Universitas Padjadjaran, 2023)
Every student has different information behavior, especially cum laude students at Riau University in 2020. Based on graduation percentage, students who hold cum laude predicate amounted to 6,22% of the total graduates in 2020. This research aimed to describe the information behavior of cum laude students at Riau University in 2020 through analysis initiation stage, selection stage, exploration stage, formulation stage, collection stage, and presentation stage. This research was qualitative through the selection of informants was based on the criteria of cum laude students with the highest scores from each faculty. The results showed that the initiation stage was based on motivation, interest, learning strategies, syllabus study, and discussion. In the selection stage, general topics were identified through mind mapping and preliminary information search. The exploration stage was carried out by searching for information in the libraries and others. In the formulation stage, the focus was on finding information with specific content, and there was a sense of optimism about collecting and using that information. The collection stage was carried out by gathering information, paying attention to information retrieval, and evaluating information. The presentation stage showed a sense of satisfaction and the process of sharing information. Every cum laude student experiences unique stages in the information-seeking process. The students at each stage the information behavior have taken advantage of all available sources of information and supported by the motivation within them.